Moonwalking - Elliott, Zetta; Miller-Lachmann, Lyn, 1956- (Farrar Straus Giroux, 2022)
In 1980s Brooklyn, new student JJ Pankowski, an autistic, punk-rock-lover, befriends Pie Velez, an Afro-Latinx math geek and graffiti artist.